Characteristics of Gelatin Produced Immersion of Tuna Bone in Lontar Vinegar from East Nusa Tenggara - Suci Istiqlaal (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
By product of tuna processing industry can potentially be used as sources of high value gelatin products. Gelatin can be obtained from acid hydrolysis of collagen. East Nusa Tenggara is a producer of lontar vinegar, however the use of this vinegar for acid hydrolysis of collagen to produce gelatin has not been determined. This study aimed to evaluate the effect of lontar vinegar and the immersion time on the characteristics of gelatin. The research used complete randomized design with two factors: types of immersion solution and immersion period. The yield, moisture, ash content, pH and viscosity were observed. The results showed that the immersion solution did not affect significantly on the yield of gelatin. Meanwhile immersion time significantly affected the yield, moisture and pH of gelatin. Immersion of the tuna bones with 3% of lontar vinegar for six weeks produced gelatin with the best characteristics.